Evaluasi Sudut Kemiringan Terhadap Pengaruh Irradiance Pada Array Photovoltaic Jenis Monocristalline - Samsurizal Samsurizal; Christiono Christiono; Andi Makkulau (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2019)
Solar cell panel technology is an alternative renewable energy source that utilizes energy from solar radiation to produce electrical energy, where one aspect that must be fulfilled is the determination of the placement location and the determination of the slope angle of the solar cell panel itself. The slope angle of the solar cell panel has a major influence on sun radiation exposure and where in each region the optimum radiation exposure of angle varies. At STT-PLN a solar power plant with a different slope angle has been installed. So it is necessary to evaluate the slope angle of irradiance in Monocristalline Type Photovoltaic Array, to observe the optimum angle of exposure to sunlight radiation field observations were carried out by taking several parameters which is angles varying from 0º to 65º with a gap per 5º, the value of the amount of radiation exposure, and the value current. Where the results of this observation found that the optimum angle in the STT-PLN environment from 0º to 65º is 25º angle with an average radiation exposure of 517 W / M² and the average current produced is 1.58 A. Keywords: Solar Power Plant, Slope Angle, Irradiance, Solar Cell Panel